PENGARUH DELAPAN GALUR HIBRIDA MENTIMUN PADA DUA LEVEL PEMUPUKAN DENGAN LIMA DAERAH PENGEMBANGAN - Uum SUMPENA (MEDIAGRO, 2015)
Interaction of several cucumber lines, fertilizer with development areas . This research was carried out in Bekasi, Karawang, Subang, Indramayu and Cirebon from Januari to April 2015, Experiment was arranged in randomized complete block design consisted of eight hybrid lines and two levels of fertilization with three replication. Hybrid lines used were  H-1, H-2, H-3, H-4, H-5, H-6, H-7 and Herkules variety control. The two levels of fertilization were recommendation dosage ( 150kg N P K per hectare ) and recomemended dosage for Riawan tani ( 225 kg  per hectare ). Plant components observed were cucumber hybrid lines productivity, number of fruit, plant height, branch diameter and number of generative branch. Results showed that  lines H-7 promised high result and was able to adapt to proper environment. Interaction of lines with location was shown by seven lines exset H-7. Lines of H-4 in Bekasi; H-4 and H-6 in Karawang; H-1 and H-4 in Subang; H-1 Indramayu and H-3 in Cirebon gained hight yield. From eight lines examined, only H-1 and H-2 represented lines with hight yield stability, genetic control on productivity. It was determined by hight estimation value heritability pf 65 %. Keywords: adaptation, lines hybrid, cucumber, West Java